Transitions agro-écologiques et tourisme - Jean-Marie Breton (Études Caribéennes)
Agro-ecological transitions, favored and supported by public authorities, contribute to facilitating the joint transformation of the agricultural and tourism sectors, in favor of innovative offers prefiguring the orientations and perspectives of responsible and sustainable "new tourisms", attentive to the environment, respectful of nature and concerned with biodiversity. Both sectors can expect from the resulting transformations reciprocal benefits, provided that the legal and financial mechanisms designed and mobilized for this purpose make it possible to meet such an objective, by promoting the adaptation of tourist behaviors and facilitating their adaptation to ecologically compatible forms of tourism.